The Relationship Between the Diversity of Growth Hormone Genes and the Body Weight of Sentul Chickens - Pratama, Shera Aditia; Depison; Gushairiyanto, Gushairiyanto (Jurnal Ilmu-Ilmu Peternakan, 2023)
This study aims to determine the diversity of growth hormone genes in Sentul chickens using PCR-RFLP. This study used 70 samples of Sentul chicken blood (35 males and 35 females). The research methods are Bodyweight and body weight gain data collection, bloodcollection, DNA extraction, and PCR-RFLP. Polymorphism analysis included genotype and allele frequencies, Hardy-Weinberg balance, and heterozygosity. The difference in the average body weight against the genotype of the GH|Msp1 gene was tested for the average difference (t-test). The average body weight of DOC - 3 months and body weight gain of DOC - 3 months in male Sentul chickens were significantly different (P <0.05) higher than female Sentul chickens. The GH|MspI gene in Sentul chickens is polymorphic. The Sentul chicken population was in Hardy-Weinberg equilibrium. Heterozygosity in the Sentul chicken population was Ho 0.228, greater than the He value of 0.213. Genotypes (++) and (+-) were significantly different (P<0.05) on body weight and body weight gain of Sentul chickens aged DOC - 3 months. The conclusion of this study, the allele frequency at the GH|MspI Sentul chicken is polymorphic with two genotypes, namely (++) and (+-), and there are two kinds of alleles (+) and (-). Chisquare test results on the GH|mspI Sentul chicken show balance Hardy-Weinberg. Heterozygosity in Sentul chickens showed diversity. The genotype of the GH|Msp1 Sentul chickens with the genotype (++) had higher body weight and body weight gain than those with the (+-) genotype